On the Constitutionalisation of Elements of the Judicial Career: What to Include and under what Considerations - Espinosa-Saldaña Barrera, Eloy (2005)
This paper examines the importance of the constitutionalization of the judicial career in Peru. The text focuses on the need for restructuring to increase the transparency and efficiency of the national judicial system. To this end, the author approaches, from a critical perspective, the reform proposals that have been prepared by working groups with the aim of determining progress in the structuring of a true judicial career in the country. Given the relevance of this task, it is important that future constitutional reforms are clearly articulated and that their implementation is effective. The tendency to make superficial regulatory changes that do not have a significant impact on judicial practice is therefore questioned. Consequently, a reorganisation is required to strengthen the justice system in a way that is comprehensive, efficient and respects constitutional principles.